SIGNIFIKANSI MONDLY LANGUAGE DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA MTsN 4 JOMBANG - Fuadah, Anisatul (Tarbawi, 2025)
The ability to speak English is a crucial skill that often faces obstacles such as lack of confidence, limited vocabulary, and monotonous learning methods. This research investigates the effectiveness of the Mondly Language application in improving the speaking skills of 9th-grade students at MTsN 4 Jombang. Using a mixed-method approach with a case study design, data were collected through observations, satisfaction surveys, interviews, and speaking tests conducted before and after the application was used. The analysis was conducted thematically and statistically, including normality tests, homogeneity tests, and Paired Samples T-Tests. The results showed that the majority of students had a high level of satisfaction with Mondly Language, particularly in terms of vocabulary and confidence. The ANOVA test and Post Hoc Tukey test indicated significant differences among student satisfaction aspects. Additionally, the Post-test scores increased significantly compared to the Pre-test scores, with an average difference of 14.571 points (t = -59.62; p < 0.05), confirming the effectiveness of Mondly in improving speaking skills. The theoretical results indicate that Mondly Language is an effective educational tool for improving vocabulary, grammar, and students' confidence in communication, offering interactive, flexible, and real-world context-based learning experiences.